HE EFFECT OF NEW USER DISCOUNT VOUCHERS, APPLICATION EASE, AND CUSTOMER SATISFACTION ON CONSUMER PURCHASE DECISIONS OF KOPI KENANGAN OUTLET TANANIMA - Arif Igo; Khumairo Fatinah Zahra (STMIK Indonesia Banda Aceh, 2026)
This study examines the influence of new user discount vouchers, application ease of use, and customer satisfaction on purchasing decisions at the Kopi Kenangan Tananima outlet. A quantitative survey was conducted involving 106 application users, and data were analyzed using multiple linear regression with IBM SPSS. The results indicate that all variables are valid and highly reliable, with normally distributed data. The coefficient of determination (R² = 0.745) shows that 74.5% of purchasing decisions are explained by the three variables. Simultaneous testing reveals a significant effect of all independent variables on purchasing decisions, while partial testing confirms that each variable has a positive and significant influence, with discount vouchers being the most dominant factor. These findings suggest that promotional strategies, application usability, and customer satisfaction significantly contribute to increasing consumer purchasing decisions.